Proof Downward Induction AM-GM

Posted on October 1, 2019
Tags: induction

AM-GM Theorem
\[ (x_1 x_2 .. x_n)^{1/n} \leq \frac{x_1 + x_2 + .. x_n}{n} \]

1 Upward induction step 1

Base step: n = 1, obvious
Base step: n = 2, obvious

\((P(k) \rightarrow P(2k) )\):

for \(k \geq 2\) IH:
\[(x_1 x_2 .. x_k)^{1/k} \leq \frac{x_1 + x_2 + .. x_k}{k}\]

Prove P(2k) is true: \[ (x_1 x_2 .. x_{2k})^{1/2k} \leq \frac{x_1 + x_2 + .. x_{2k} }{2k} \]

Thoughts:

Get stuck !! How do we show this inequality.

IMPORTANT TECHNIQUE - IH(2) meaning induction hypothesis with n=2.

Observe \((\frac{\color{red}{{}^{+}A \times {}^{+}B}}{k^2})^{k}\)

\((\frac{\color{red}{{}^{+}A \times {}^{+}B}}{k^2})^{k} \leq (\frac{1}{k^2})({\color{red}{(\frac{{}^{+}A \times {}^{+}B}{2})^{2}}})^{k} = (\frac{{}^{+}A + {}^{+}B}{2k})^{2k}\)

QED: \((\frac{{}^{+}A \times {}^{+}B}{k^2})^{k} \leq (\frac{{}^{+}A + {}^{+}B}{2k})^{2k}\)

Thoughts: Don’t fall in to the trap of believing IH should only be used with obvious cases like n-1, n/2
IH(2) is the crux of this proof.

2 Downward induction step 2

\((P(k) \rightarrow P(k-1) )\):
After shifting complexity LHS to RHS:

IMPORTANT WRITE OUT \(x_{n-1}\) instead of just abstracting it into the ellipse.If not you will hit a roadblock when using IH.
\(x_1 + x_2 + .. x_{n}\) is BAD.
\(x_1 + x_2 + .. x_{n-1}+x_{n}\) is GOOD.

let \(C^+ = x_1 + x_2 + ..x_{n-1}\)
let \(C^{\times} = (x_1 x_2 ..x_{n-1})\)

IH: \[ (x_1 x_2 ..x_{n-1} x_n) \leq (\frac{x_1 + x_2 + .. x_{n-1} + x_n}{n})^{n} \]

\[ (C^{\times} \times x_n) \leq (\frac{C^+ + x_n}{n})^n \tag{IH}\]

Goal: \[ (x_1 x_2 .. x_{n-1}) \leq (\frac{x_1 + x_2 + .. x_{n-1}}{n-1})^{n-1} \]

\[ (C^{\times}) \leq (\frac{C^+ }{n-1})^{n-1} \tag{Goal} \]

2.1 Pause Real Proof: Reverse meta-Rewrite Goal

Find an expression that fits the criteria to use \((IH)\) : \[(x_1 x_2 .. x_{n-1}\times\framebox{}) \leq (\frac{x_1 + x_2 + .. x_{n-1}+ \framebox{}}{n})^{n} \tag{1}\]

Relating IH back to the Goal :
Algebraic manipulation: multiply bothside of \((Goal)\) with \(\framebox{}\)
\[(x_1 x_2 .. x_{n-1}\times\framebox{}) \leq \framebox{}\times(\frac{x_1 + x_2 + .. x_{n-1}}{n-1})^{n-1}\tag{2}\]

Combined (1) and (2):
Meta-choose the non-striked out combination because it leads us closer to our goal.
How did we get that equation? It’s a Meta-choice, meaning later in the real proof we HOPE to achieve this equation . \[\xcancel{(x_1 x_2 .. x_{n-1}\times\framebox{}) \leq \framebox{}\times(\frac{x_1 + x_2 + .. x_{n-1}}{n-1})^{n-1} \leq(\frac{x_1 + x_2 + .. x_{n-1}+ \framebox{}}{n})^{n}}\] \[(x_1 x_2 .. x_{n-1}\times\framebox{}) \leq (\frac{x_1 + x_2 + .. x_{n-1}+ \framebox{}}{n})^{n}\leq \framebox{}\times(\frac{x_1 + x_2 + .. x_{n-1}}{n-1})^{n-1}\tag{3}\]

New Goal by multiplying \((3)\) by \(\frac{1}{\framebox{}}\):
\[ (x_1 x_2 .. x_{n-1}) \leq (\frac{1}{\framebox{}})(\frac{x_1 + x_2 + .. x_{n-1}+ \framebox{}}{n})^{n} \leq (\frac{x_1 + x_2 + .. x_{n-1}}{n-1})^{n-1}\tag{4}\]

Thoughts:

  • Find syntatic similarity of the three expression in goal.
    • \(x_1 + x_2 + .. x_{n-1}\)
  • Renaming
    • \(A = x_1 + x_2 + .. x_{n-1}\)

Renamed Goal: \[ (x_1 x_2 .. x_{n-1}) \leq (\frac{1}{\framebox{}})(\frac{A + \framebox{}}{n})^{n} \leq (\frac{A}{n-1})^{n-1}\tag{Renamed(Goal)}\]

Try: \(\framebox{} = \frac{A}{n-1}\)

  • Backenvelop calculations to see where this could go:
    • \(\frac{A + \framebox{}}{n} =\frac{A+\frac{A}{n-1}}{n} = \frac{\frac{An-A+A}{n-1}}{n}=\frac{A}{n-1}\)
    • Looks good

2.2 Resume Real Proof

Solving Goal:

\[(x_1 x_2 .. x_{n-1}) \leq (\frac{1}{\frac{A}{n-1}})(\frac{A}{n-1})^{n}\leq (\frac{A}{n-1})^{n-1}\]

\[(x_1 x_2 .. x_{n-1}) \leq (\frac{A}{n-1})^{-1}(\frac{A}{n-1})^{n}\leq (\frac{A}{n-1})^{n-1}\]

\[(x_1 x_2 .. x_{n-1}) \leq (\frac{A}{n-1})^{n-1}\leq (\frac{A}{n-1})^{n-1}\]

Backtrack Meta:

Reverse operation fill in \(\framebox{}\) in \((1)\) to get our \(new IH\)

\[x_n = \frac{A}{n-1}\]

\[(x_1 x_2 .. x_{n-1}\frac{A}{n-1}) \leq (\frac{x_1 + x_2 + .. x_{n-1}+ \frac{A}{n-1}}{n})^{n} \tag{new IH}\]

3 Step 3 Combining results from Upwards and Downward induction

QED Combining Upward and Downward induction constitutes a full proof the inequality is true for all naturals.

4 Aside